Keefektifan Penerapan Strategi Pembelajaran Berbasis Humor Pada Materi Genetika Terhadap Minat dan Hasil Belajar Siswa Kelas XII SMA Negeri 11 Makassar - Fitri, Suci Ramdani; Hamka L., Hamka L.; Saenab, Sitti (Biology Teaching and Learning, 2018)
Abstract.  This research is pra-experimental design that aims to determine effectiveness of student‟s learning interest and outcomes toward learning strategies based humor on genetic subject of student grade XII SMA Negeri 11 Makassar. Independent Variabe in this research is the application of learning strategies based humor on genetic subject, while the dependent variable is the student‟s learning interest and outcomes of genetic subject. The population in this study were all students of class XII SMA Negeri 11 Makassar with totally seven classes, while the sample is student‟s grade XII with totally 66 students. Pretest-posstest was used as data collection technique, by used a questionnaire of student learning interest and genetic  achivement test. Data analysis technique that used is a descriptive analysis using the n-gain and inferential analysis using paired sample t-test. Based on the descriptive analysis showed that n-gain value of student‟s interest and learning outcomes of genetics achieve an increase of >75% in the category of medium-high, which are respectively 77% and 92%, whereas the inferential analysis using SPSS showed a significance value 0.000 > α = 0.05 which indicates H0 isrejected and H1 is accepted, that the known application learning strategies based humor on genetic subject  has a significant influence (real) towards the student‟s learning interests  and outcomes. Therefore, based on these two data analysis concluded that the learning strategies based humor on genetic subject effectively to student‟s learning interest and outcomes of student of grade XII SMA Negeri 11 Makassar. Keywords: learning strategies based humor, student’s interest, student outcomes, genetic.